Technology Entrepreneurship Project (ENT 600) : Decathlon Group / Mohamad Syafiq Shah M. Nasser Subramaniam - M. Nasser Subramaniam, Mohamad Syafiq Shah (2021)
This is an opportunity for us as a student to learnt technology entrepreneurship subject for this semester. This is because we can apply for what we study for this whole semester on this subject for us in the future and also can be applied all the theories in the real and practical situation. As a student in UiTM Perlis, it is a part of a case study for everyone that taking subject technology entrepreneurship to undergo a case study project. Because we have a case study like this, I got the chance to research a corporate entity that manufactures a product that provide sport equipment, which is name Decathlon Group, a sports retailer. First of all, the general information regarding the corporate has been collected through the primary and the secondary sources. The objective of the project is to figure on the background, organizational structure, products and services that Decathlon provides. Next, in this case study I should analyses the strength, weaknesses, opportunities, and threats of this company in the real business world by using SWOT analysis. The product that attract my interest is the tracksuit at there. Here, I will explain about problem of that tracksuit that attract my interest at there. First of all, the problem that I have discovered is the colour of the Kiprun men’s breathable running trousers is easily to become fade. Next, the product is not are water resistance product so it can easily become wet when sweating. Lastly, it can easily tear when we are doing outdoor activity. So in this study, I will be explaining regarding the all problems that has and also will be discussing on the alternatives to makes a good solutions to the product.